Creep fatigue models of solder joints: A critical review. (April 2016) - Wong, E.H.; van Driel, W.D.; Dasgupta, A.; Pecht, M.
Abstract: The goal of creep fatigue modelling is the compounding of the damage caused by creep and fatigue mechanisms. The different approaches for compounding these damage mechanisms have led to several different creep fatigue models: (i) ignore fatigue damage — the creep ductility (energy density) exhaustion models; (ii) lumping plastic and creep strain (energy) into inelastic strain (energy) — the model of Dauvearx's crack initiation and propagation; (iii) linearly sum fatigue and creep damage — the model of linear damage summation; (iv) model creep and fatigue damage using a common parameter — the models of fracture mechanics; (v) partition damage into fatigue, cyclic creep, and cyclic creep-fatigue interaction — strain range/energy partitioning models; (vi) model creep and fatigue damage using a common parameter at rates that are dependent on the current state of damage — the model unified damage; (vii) model creep and fatigue damage using separate damage parameters — the mechanism based model; and (viii) integrate creep damage into the fatigue equation — creep modified strain-life equations. The rigour of the approaches increases from (i) to (vii). The creep modified strain-life equation requires no evaluation of creep strain and facilitates design analysis and evaluation of acceleration factors; however, its rigour depends on the choice of the creep functions. The unified equation is capable of covering the full spectrum of creep-fatigue from pure fatigue to pure creep rupture. Highlights: Review of creep fatigue models in the power and aerospace communities Critical review of creep fatigue models in the electronic assembly communities Introduction of new creep fatigue model — the unified equation Benchmarking of creep-modified fatigue models